2014
DOI: 10.1177/2325957414524025
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Me Screen for HIV? Perceived Barriers and Facilitators to Conducting Recommended Routine HIV Testing among Primary Care Physicians in the Southeastern United States

Abstract: The Centers for Disease Control and Prevention have recommended routinely testing patients (aged 13–64) for HIV since 2006. However, many physicians do not routinely test. From January 2011- March 2012, we conducted 18 in-depth individual interviews and explored primary care physicians’ perceptions of barriers and facilitators to implementing routine HIV testing in North Carolina. Physicians’ comments were categorized thematically and fell into five groups: policy, community, practice, physician and patient. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 28 publications
2
63
0
6
Order By: Relevance
“…Only approximately 10% reported adhering to the recommendation. 55,56 Barriers identified by these physicians included current HIV-related policies (eg, third-party reimbursement, requirement for written consent), stigma and lack of confidentiality in nonurban communities, practice financial environment, physician attitudes, and patient acceptance. 56 …”
Section: The Hiv Continuum Of Care In the Nonurban Contextmentioning
confidence: 99%
“…Only approximately 10% reported adhering to the recommendation. 55,56 Barriers identified by these physicians included current HIV-related policies (eg, third-party reimbursement, requirement for written consent), stigma and lack of confidentiality in nonurban communities, practice financial environment, physician attitudes, and patient acceptance. 56 …”
Section: The Hiv Continuum Of Care In the Nonurban Contextmentioning
confidence: 99%
“…However, persons at risk for HIV, and therefore potential candidates for pre-exposure prophylaxis (PrEP), typically receive care from primary care clinicians, who may feel discomfort with prescribing PrEP and that it may not fall within their clinical purview (Hoffman et al, 2015; Krakower, Ware, Mitty, Maloney, & Mayer, 2014). The literature also indicates educational (i.e., lack of knowledge or misperceptions) (Sison et al, 2013) and financial barriers (i.e., inadequate reimbursement) (Korthuis et al, 2011; White et al, 2015) to primary care physicians offering HIV testing and counseling. Many primary care physicians remain unaware of CDC’s HIV testing recommendations (Arya et al, 2014), and increased educational and outreach opportunities not only for HIV testing but also for HIV management may be required.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent qualitative study published by White et al found that physicians find it advantageous for patients to ask for the HIV test. 23 Such patient-initiated discussions could help overcome some of physicians’ interpersonal barriers that hinder HIV testing discussions. 17 Furthermore, patients who are more involved and actively participate in their physicians’ appointments are met with more patient-centered communication from and are more favorably perceived by their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a 2014 study reported that physicians believe public HIV testing campaigns can “legitimize” testing and decrease stigma. 23 Physicians appear to be open to methods of promoting HIV testing that do not ostracize or profile patients but that indicate HIV as an acceptable topic of discussion for all patients.…”
Section: Discussionmentioning
confidence: 99%